POTENSI UBI JALAR SEBAGAI BAHAN BAKU INDUSTRI PANGAN - -, Rosidah (Teknobuga, 2010)
Sweet potato is one of the unique food commodities because they have severalvarieties with characteristics and advantages of each, there are sweet white potatoes,yellow sweet potatoes, red sweet potato and purple sweet potatoes. The potential ofsweet potato as raw material for food industry is very large, given the abundantresources available materials, for easy cultivation and harvest time is short, other thanthat sweet potatoes have a high flexibility in the processing, complete nutritionalcontent even some substances such very important for the physiological functioning ofthe body because anthosianin and carotene as an antioxidant and rapinasa fiber thatserves prebiotic. Other potential of sweet potato is the public acceptability of theproduct from sweet potatoes, which will be appreciated by the public because thebasic ingredients known to the communitys enough just need to be innovative.Diversification of sweet potato that can be developed by the food industry including,various cookies, cakes, chips, ice cream and baby cereal.Keywords: Potential of sweet potato, food industryUbi jalar merupakan salah satu komoditas bahan pangan yang unik karena memilikibeberapa varietas dengan karakteristik dan keunggulan masing-masing, ada ubi jalarputih, ubi jalar kuning, ubi jalar merah dan ubi jalar ungu. Potensi ubi jalar sebagaibahan baku industry pangan sangat besar, mengingat sumber daya bahan tersediamelimpah, karena budi daya yang mudah dan masa panen yang singkat, selain itu ubijalar juga memiliki fleksibilitas yang tinggi dalam pengolahan, kandungan zat gizinyacukup lengkap bahkan beberapa zat diantaranya sangat penting bagi tubuh karenaberfungsi fisiologis yaitu anthosianin dan karatenoid sebagai anti oksidan serta seratrapinasa yang berfungsi prebiotik.Potensi lain dari ubi jalar adalah daya terima masyarakat terhadap produk dari ubijalar yang akan disukai masyarakat karena bahan dasar sudah cukup dikenaldimasyarakat hanya perlu inovatif. Diversifikasi ubi jalar yang dapat dikembangkanoleh industry pangan di anataranya ; aneka cookies, cake, chip, ice cream dan buburbayi.Kata Kunci : Potensi ubi jalar, Industri pangan